2020
DOI: 10.1021/acschembio.9b00923
|View full text |Cite
|
Sign up to set email alerts
|

2′-Fluorinated Hydantoins as Chemical Biology Tools for Base Excision Repair Glycosylases

Abstract: The guanine oxidation products, 5-guanidinohydantoin (Gh) and spiroiminodihydantoin (Sp) are mutagenic and toxic base lesions that are removed by Fpg, Nei, and the Nei-like (NEIL) glycosylases as the first step in base excision repair (BER). The hydantoins are excellent substrates for the NEIL glycosylases in a variety of DNA contexts beyond canonical duplex DNA, implicating the potential impact of repair activity on a multitude of cellular processes. In order to prepare stable derivatives as chemical biology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Structural studies of Ed and UE NEIL1 bound to a Tg duplex showed that the Lys242 or Arg242 side chain, within the lesion recognition loop of NEIL1, interacts with the Tg base . However, the two isoforms exhibited similar affinity in electrophoretic mobility shift assays (EMSAs) to duplex DNA-containing noncleavable synthetic analogues, 2′-fluorothymidine glycol (FTg) and 2′F-guanidinohydantoin (FGh). , These results suggested that the origin of the differential lesion processing is related to a kinetic step rather than lesion binding affinity. The biological implications of NEIL1 recoding have not been fully elaborated; however, conspicuously, multiple myeloma cells overexpressing Ed NEIL1 proliferated at significantly higher rates and presented hallmark signatures associated with unrepaired double-strand breaks …”
Section: Introductionmentioning
confidence: 99%
“…Structural studies of Ed and UE NEIL1 bound to a Tg duplex showed that the Lys242 or Arg242 side chain, within the lesion recognition loop of NEIL1, interacts with the Tg base . However, the two isoforms exhibited similar affinity in electrophoretic mobility shift assays (EMSAs) to duplex DNA-containing noncleavable synthetic analogues, 2′-fluorothymidine glycol (FTg) and 2′F-guanidinohydantoin (FGh). , These results suggested that the origin of the differential lesion processing is related to a kinetic step rather than lesion binding affinity. The biological implications of NEIL1 recoding have not been fully elaborated; however, conspicuously, multiple myeloma cells overexpressing Ed NEIL1 proliferated at significantly higher rates and presented hallmark signatures associated with unrepaired double-strand breaks …”
Section: Introductionmentioning
confidence: 99%
“…23,24 The introduction of F atoms to the sugar of DNA has a large impact on DNA stability and activity as the modification of the sugar moiety affects the electronegativity of the base through the stereoelectronic effect. 25,26 Therefore, we speculate that Fsubstituted bases have a strong adsorption capacity on the surface of AuNPs. To evaluate the effect of F atoms on Au/ FDNA stability, a series of Au/F x DNA (x = 1, 2, 3) were prepared (Scheme 1, Scheme 2, Figure S1, and Table 1).…”
mentioning
confidence: 96%
“…This prediction is supported by the finding that both 2′-mono-and difluoro substitutions of deoxyuridine in oligonucleotides prevented glycosylase mediated base excision. 36 Interestingly, some bifunctional glycosylase activities capable of removing the base of a 2′-F-substituted analogue have been detected, 37 but these enzymes could not carry out the required cleavage of the 2′-C−F bond in the arabino-configuration (which would be one of the two fluorines during the subsequent β-elimination step (see Figure S2)), stalling the enzyme at the site of the damage. 37 This is reminiscent of the mechanisms of inactivation of TS and MTase by fluoropyrimidines 31−33 discussed above, which results from the lack of cleavage of the C−F bond in the 5position of the respective substrates (see Figure 6).…”
mentioning
confidence: 99%